The Dryland Research Project at Indore, 1974-80: An International Innovation in Rural Technology Transfer - Clark, Norman; Clay, Edward J. (Brighton, England: Institute of Development Studies Publications, 1986)
This paper explores an alternative model of technology transfer as exemplified by the Indore Dryland Research project; and some of the lessons of the Indore experiment, concluding that this type of technology transfer model should be given more prominence in agricultural development planning in poor countries.
" DP 222 November 1986."
At head of title: Agriculture and rural problems.
Includes bibliographical references (p. 30-32).
ne 9/04/2018
Loans
Keywords: Agriculture